Land concentration and rural poverty - Griffin, Keith B. (London : Macmillan, 1976)
This volume focuses on the distribution of land-ownership, an institutional variable which in the previous study was found to be central to an understanding of the pace and consequences of technical change in agrarian societies. This text is preoccupied with poverty rather than technology. The theme is centered on the distribution of income in the agricultural sector and the standard of living of the majority of the rural population which are greatly affected by the degree of land concentration. The book is divided into three: North Africa; Latin America and Asia.
Includes bibliographical references and index.
rpm 27/09/2017
Loans
Keywords: Land reform; Agriculture